Puf-trng for a Secure Industry 4.0 - Eka Harsono; Chong Ming Tang (Conference Series, 2020)
Modern technology such as IoT has made a significant change in the industry. By enabling communication between smart machines, the automation process would be more dynamic and adaptive. It will enable the machines to perform necessary tasks based on real data received from the other hardware. Additionally, the data recorded in the machines will further help the engineer to easily check the problem and the information needed for future development. However, unsecured data exchanges will compromise the data and the security of the devices. Popular security measures such as encryption and decryption are commonly used to solve the information exchange. However it is possible to further improve the performance for both encryption and decryption process by implementing a TRNG (True Random Number Generator). TRNG requires a strong entropy such as the proposed Physical Unclonable Function (PUF) which produces a response based on the physical variations of device parameters during the fabrication process.